Comparing Seasonal Trends in Coronavirus Disease 2019 Patient Data at a Quaternary Hospital in New York City. (26th March 2021) - Tandon, Pranai; Leibner, Evan; Ahmed, Sanam; Acquah, Samuel O.; Kohli-Seth, Roopa
Abstract : Coronavirus disease 2019 has been a worldwide pandemic since early 2020 with New York City being the epicenter in the United States during early 2020. Although cases of decreased coronavirus disease 2019 during the summer, cases began to rise once more in the fall-winter period. Little is known about trends in patient characteristics, medical care, and outcome between these time periods. We report initial patient characteristics and outcomes from a large quaternary referral center in New York City between Spring (March to June), Summer (July to September), and Winter (October to December), including prevalence of renal failure, respiratory failure, and mortality; stratified across several key populations of interest including all patients, ICU patients, those requiring of noninvasive positive pressure ventilation and high-flow nasal cannula, and those intubated in each time period.